2019
DOI: 10.4236/ojn.2019.94040
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adherence to Antiretroviral Therapy among HIV Positive Adolescents at Adult Infectious Diseases Center in Lusaka, Zambia

Abstract: Background: Non-adherence to combination antiretroviral therapy leads to drug resistance, treatment failure and increased morbidity and mortality among HIV positive adolescents. The aim of this study was to assess factors influencing adherence to combination antiretroviral therapy among HIV positive adolescents at Adult Infectious Disease Center in Lusaka, Zambia. Methodology: A descriptive quantitative cross sectional study was conducted on 173 adolescent respondents on antiretroviral therapy who were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
0
1
Order By: Relevance
“…Furthermore, due to cultural barriers, women in this study area may have had difficulties disclosing their status, thus meaning that they need to hide while taking their medications. On the other hand, this study is not in line with a study done in Zambia in which male adolescents were found to be two times more non-adherent than female adolescents [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, due to cultural barriers, women in this study area may have had difficulties disclosing their status, thus meaning that they need to hide while taking their medications. On the other hand, this study is not in line with a study done in Zambia in which male adolescents were found to be two times more non-adherent than female adolescents [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%